INDUKSI KALUS DAN REGENERASI TANAMAN DARI KULTUR ANTERA PADI Fl HYBRID (ORYZA SATIVA L.) - Dwimahyani, Ita; Ishak, Ishak; Sobrizal, Sobrizal (BERITA BIOLOGI, 2000)
A haploid breeding program was initiated to develop doubled haploid blast tolerance rice breeding via anther culture.Blast tolerant variety (Laka) was crossed with Kencana Bali (sensitive to blast).Anthers from F1 were cultured on two kind of media (combination of N6 macro salt and MS micro salt) containing 1 mg/l NAA + 0,1 mg/l kinetin called medium-1 and another one containing 1 mg/l 2,4-D + 0,1 mg/l kinetin called medium-2.Anthers were treated with cold shock (4 Â°C)for 5 and 10 days before cultured.Results of experiment showed that F1 plants derived anthers were able to form call Number ofplantlets were produced during anthers culture consisted of 482 green plants and 50 albinos. Most of green plants did not produced root.Root growth of plantlets were induced with 1.5-4.5 mg/l IBA in MS medium.